The distribution of plant consumption traits across habitat types and the patterns of fruit availability suggest a mechanism of coexistence of two sympatric frugivorous mammals. Issue 8 (1st April 2019) - Tédonzong, Luc Roscelin Dongmo; Willie, Jacob; Tagg, Nikki; Tchamba, Martin N.; Angwafo, Tsi Evaristus; Keuko, Ada Myriane Patipe; Kuenbou, Jacques Keumo; Petre, Charles‐Albert; Lens, Luc
Abstract: Understanding the mechanisms governing the coexistence of organisms is an important question in ecology, and providing potential solutions contributes to conservation science. In this study, we evaluated the contribution of several mechanisms to the coexistence of two sympatric frugivores, using western lowland gorillas ( Gorilla gorilla gorilla ) and central chimpanzees ( Pan troglodytes troglodytes ) in a tropical rainforest of southeast Cameroon as a model system. We collected great ape fecal samples to determine and classify fruit species consumed; we conducted great ape nest surveys to evaluate seasonal patterns of habitat use; and we collected botanical data to investigate the distribution of plant species across habitat types in relation to their "consumption traits" (which indicate whether plants are preferred or fallback for either gorilla, chimpanzee, or both). We found that patterns of habitat use varied seasonally for both gorillas and chimpanzees and that gorilla and chimpanzee preferred and fallback fruits differed. Also, the distribution of plant consumption traits was influenced by habitat type and matched accordingly with the patterns of habitat use by gorillas and chimpanzees. We show that neither habitat selection nor fruit preference alone can explain the coexistence of gorillas and chimpanzees, but that considering together the distribution of plant consumption traits of fruiting woody plants across habitats as well as the pattern of fruit availability may contribute to explaining coexistence. This supports the assumptions of niche theory with dominant and subordinate species in heterogeneous landscapes, whereby a species may prefer nesting in habitats where it is less subject to competitive exclusion and where food availability is higher. To our knowledge, our study is the first to investigate the contribution of plant consumption traits, seasonality, and habitat heterogeneity to enabling the coexistence of two sympatric frugivores. OPEN RESEARCH BADGES: This article has earned an Open Data Badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttps://datadryad.org/resource/doi:10.5061/dryad.ms65f29 . Abstract : The distribution of resources have often been used to evaluate the mechanism underlying the coexistence between two organisms and one of the weaknesses is that studies do not take into account the quality of the resource to the animal species being considered. We defined consumption traits of fruiting plant species consumed based on whether it is preferred or a fallback to the species. We demonstrated that the distribution of plant consumption traits in different habitat types allow the consideration of the interaction between two niche axes (diet and nesting habitat use), as a mechanism of coexistence between two frugivorous mammals.